Electrospun PU/MgO/Ag Nanofibers for Antibacterial Activity and Flame Retardency. (July 2023) - Mamtha, V.; Murthy, H. N. Narasimha; Raj, V. Pujith; Tejas, Prashantha; Puneet, C. S.; Venugopal, Achyutha; AanMankunipoyil, Sham; Manjunatha, C.
Antibacterial activity and fire retardation are equally desired for protective clothing. For achieving this, AgNP and MgO are independently researched as nanofillers in Polyurethane based electrospun nanofibers and their synergistic effect is scarcely addressed. This article reports synthesis and characterization of MgO of 70.01 nm and AgNP of 51 to 76 nm by solution combustion and hydrothermal routes respectively and their incorporation in electrospinning of Polyurethane. Flow rate 1 ml/hr, applied voltage 13 kV, tip to collector distance 15 cm were adopted for the electrospinning. Nanofibers of 65 nm were obtained for PU/MgO (3 wt. %) and 106 nm for PU/MgO (3 wt. %)/Ag (1 wt. %). Addition of MgO increased the melting point, after flame time and afterglow time. Incorporation of AgNP improved antibacterial activity. PU/MgO/Ag (2 wt. %) exhibited zone of inhibition of 2.1 cm and 3 cm against E. Coli and S. Aureus, respectively.